Le français, langue colonisatrice - Horányi, Lilla (Verbum – Analecta Neolatina, 2013)
In this paper, we examine how the Other is represented in two exotic novels of Georges Simenon, Le Coup de lune (1933) and Le Blanc à lunettes (1937), which take place in Africa and deal with the colonial experience of two European men. Through a postcolonial reading, we show that the representation of the Other is related to the notions of absence, silence and look. Our analysis will also reveal to what extent a rapprochement is possible between European colonizers and Native people.